Politics, power and the Internet: New possibilities against old dilemmas - Sierra, Jerónimo Ríos (University Santo Tomás, Bogotá, 2015)
Internet and new technologies have reconfigure the relationship between thestate and civil society, specially the relationship between power and shaped bypolitics. Under this situation converge new possibilities and old dilemmas thatmust adapt to changing, current dynamics, as transterritoriality of socialmovements, the (auto) or mass communication redefining the meaning ofmodernity. The civil society develops, thanks to the Internet, organizational, communicationand participation framework that serves optimum culture broth for therepresentation of new disputes against a nation-state that is still, despiteeverything, the benchmark for the analysis of power formally institutionalized.